Mass Spectrometry in Life Sciences and Clinical Laboratory - Mitulović, Goran (IntechOpen, 2021)
Mass spectrometry is a state-of-the-art tool for basic biological research and applied clinical diagnostics. This book covers sample preparation for mass spectrometric analysis for proteomics, clinical studies, and food analysis. In addition, it explores possible directions for further developing the technology and its potential applications.